AB0417 EFFICACY AND SAFETY OF TOFACITINIB IN PATIENTS WITH RHEUMATOID ARTHRITIS ACCORDING TO DURATION OF PRIOR CSDMARD TREATMENT AND NUMBER OF PRIOR CSDMARDS: A POST HOC ANALYSIS OF PHASE 3 AND PHASE 3B/4 TRIALS. (June 2019) - Aletaha, Daniel; Gomez-Reino, Juan Jose; Burmester, Gerd Rdiger; Vollenhoven, Ronald van; Luis Rivas, Jose; Benkhalifa, Salim; Dahl, Palle; Shi, Harry; Wang, Lisy
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). Previous analyses have reported greater improvements in efficacy outcomes with tofacitinib 5 mg twice daily (BID) conventional synthetic DMARDs (csDMARDs) in patients (pts) with early vs established RA. 1, 2 Objectives: To evaluate the efficacy and safety of tofacitinib in pts with RA, stratified by prior csDMARD treatment duration and number of prior csDMARDs. Methods: This was a post hoc analysis of pooled data from 4 Phase (P)3 trials (ORAL Scan [NCT00847613 ]; ORAL Solo [NCT00814307 ]; ORAL Sync [NCT00856544 ]; ORAL Standard [NCT00853385 ]) and 1 P3b/4 trial (ORAL Strategy [NCT02187055 ]) of tofacitinib in pts with RA and an inadequate response to =1 DMARD. Pts treated with tofacitinib 5 mg BID as monotherapy or with csDMARDs were included. Outcomes were evaluated according to csDMARD treatment duration (=1, 12, >2 years *y+) and number of csDMARDs (1, 2, 3, =4) prior to baseline (BL). Efficacy outcomes assessed at Months (M)3, 6 and 12 were: change from BL (?) in CDAI and HAQ-DI, and rates of CDAI-defined low disease activity (LDA; =10) and remission (=2.8). Safety outcomes, including treatment-emergent adverse events (AEs), serious AEs (SAEs) and AEs of special interest, were evaluated throughout the studies. Results: In total, 1584 pts were included in the analysis; of these, 27.2% (n=431) had received csDMARDs for =1 y, 20.5% (n=325) for 12 y, and 52.1% (n=825) for >2 y prior to BL (duration unknown for 3 pts). Roughly half (53.2%, n=842) had received 1 prior csDMARD; 26.4% (n=418), 13.8% (n=219) and 6.6% (n=105) had received 2, 3 and =4 prior csDMARDs, respectively. Most pts had previously received MTX (50.8%, n=805) or MTX + other csDMARDs (46.3%, n=733); 2.9% (n=46) received other csDMARDs only. Mean BL CDAI and HAQ-DI scores were similar, irrespective of prior csDMARD treatment duration or number of prior csDMARDs (Table). Generally, up to M12, no trends were observed for ?CDAI, ?HAQ-DI or CDAI LDA rates regardless of prior csDMARD treatment duration or number of prior csDMARDs (Table). When CDAI remission rates data were stratified by csDMARD treatment duration, no differences between pt groups were observed at M3 and M6; however, a numerically higher proportion of pts with prior csDMARD treatment duration =1 y achieved remission at M12 vs 12 y and >2 y pts. Use of fewer prior csDMARDs appeared to be associated with higher remission rates up to M12. Although safety outcomes were similar when data were stratified by prior csDMARD treatment duration, there was generally a trend for increased rates of AEs, SAEs and AEs of special interest (serious infections, herpes zoster and opportunistic infections [excluding TB]) with increasing number of prior csDMARDs (Table). Conclusion: In this post hoc analysis of pooled data from P3 and P3b/4 trials, no differences in the efficacy or safety of tofacitinib 5 mg BID were observed when pts were stratified by prior csDMARD treatment duration. Although pt numbers were small, use of fewer prior csDMARDs may be associated with improved remission rates and safety outcomes for pts treated with tofacitinib. References: [1] Hall S et al. Arthritis Rheum 2016; 68 (S10): 1999-2001. [2] Fleischmann RM et al. RMD Open 2016; 2: e000262. Acknowledgement: Study sponsored by Pfizer Inc. Medical writing support was provided by Kirsten Woollcott of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: Daniel Aletaha Grant/research support from: AbbVie, Bristol-Myers Squibb, and MSD, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Medac, Merck, MSD, Pfizer Inc, Roche, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Medac, Merck, MSD, Pfizer Inc, Roche, and UCB, Juan Jose Gomez-Reino Grant/research support from: Biogen, Gilead, Eli Lilly, Merck Sharp & Dohme, Pfizer, Roche, Consultant for: Biogen, Gilead, Eli Lilly, Merck Sharp & Dohme, Pfizer, Roche, Gerd Rdiger Burmester Consultant for: Roche, Sanofi-Genzyme, Speakers bureau: Roche, Sanofi-Genzyme, Ronald van Vollenhoven Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, GSK, Pfizer Inc, Roche and UCB, Consultant for: AbbVie, AstraZeneca, Biotest, Bristol-Myers Squibb, Celgene, Crescendo, Eli Lilly, GSK, Janssen, Merck, Novartis, Pfizer Inc, Roche, UCB and Vertex, Jose Luis Rivas Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Salim Benkhalifa Shareholder of: Pfizer SAS, Employee of: Pfizer SAS, Palle Dahl Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Harry Shi Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Lisy Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc